Community health workers at the dawn of a new era - Joseph M. Zulu; Henry B. Perry (BMC, 2021)
Abstract Background There is now rapidly growing global awareness of the potential of large-scale community health worker (CHW) programmes not only for improving population health but, even more importantly, for accelerating the achievement of universal health coverage and eliminating readily preventable child and maternal deaths. However, these programmes face many challenges that must be overcome in order for them to reach their full potential. Findings This editorial introduces a series of 11 articles that provide an overview highlighting a broad range of issues facing large-scale CHW programmes. The series addresses many of them: planning, coordination and partnerships; governance, financing, roles and tasks, training, supervision, incentives and remuneration; relationships with the health system and communities; and programme performance and its assessment. Above all, CHW programmes need stronger political and financial support, and this can occur only if the potential of these programmes is more broadly recognized. The authors of the papers in this series believe that these challenges can and will be overcome-but not overnight. For this reason, the series bears the title "Community Health Workers at the Dawn of a New Era". The scientific evidence regarding the ability of CHWs to improve population health is incontrovertible, and the favourable experience with these programmes at scale when they are properly designed, implemented, and supported is compelling. CHW programmes were once seen as a second-class solution to a temporary problem, meaning that once the burden of disease from maternal and child conditions and from communicable diseases in low-income countries had been appropriately reduced, there would be no further need for CHWs. That perspective no longer holds. CHW programmes are now seen as an essential component of a high-performing healthcare system even in developed countries. Their use is growing rapidly in the United States, for instance. And CHWs are also now recognized as having a critically important role in the control of noncommunicable diseases as well as in the response to pandemics of today and tomorrow in all low-, middle-, and high-income countries throughout the world. Conclusion The promise of CHW programmes is too great not to provide them with the support they need to achieve their full potential. This series helps to point the way for how this support can be provided.